Rehabilitation of a Full-Arch Patient with Cemented Metal-Ceramic Multiple Prostheses on Implants: A Case Report - Guilherme, Adérico Santana; Moreira, Yasmin Milhomens; Martins, Rhadija Victoria Mendonça; Aguiar, Bárbara Lima de (Brazilian Dental Science, 2024)
Objective: To report a clinical case of a female patient rehabilitated with Cemented Metal-Ceramic Multiple Prostheses on Implants in the upper arch. Materials and Methods: A multidisciplinary approach was employed, utilizing various clinical skills to achieve satisfactory outcomes in the rehabilitation of a fully edentulous patient. The treatment plan involved the use of cemented metal-ceramic prostheses, with a focus on optimizing the positioning of the crown margins to ensure periodontal health. Results: The use of cemented metal-ceramic multiple prostheses effectively addressed the patient’s aesthetic concerns by eliminating screw access holes and ensuring the continuity of the ceramic material. The supragingival positioning of the crown margins prevented excess cement in the peri-implant sulcus, promoting periodontal health. The final prostheses provided excellent aesthetics and functionality, leading to enhanced patient satisfaction. Conclusion: The choice of cemented implant-supported prostheses represents a highly effective approach for treating edentulism. This method offers clinical benefits, such as increased retention and improved esthetic outcomes, while also positively impacting the patient’s quality of life. KEYWORDS Dental implants; Dental implant-supported prosthesis; Fixed partial prosthesis; Prostheses and implants; Oral rehabilitation.